2017
DOI: 10.1002/mabi.201600490
|View full text |Cite
|
Sign up to set email alerts
|

Combined Delivery of a Lipopolysaccharide‐Binding Peptide and the Heme Oxygenase‐1 Gene Using Deoxycholic Acid‐Conjugated Polyethylenimine for the Treatment of Acute Lung Injury

Abstract: A ternary complex comprising plasmid DNA, lipopolysaccharide-binding peptide (LBP), and deoxycholic acid-conjugated polyethylenimine (PEI-DA) is prepared for combinational therapy of acute lung injury (ALI). The LBP is designed as an anti-inflammatory peptide based on the lipopolysaccharide (LPS)-binding domain of HMGB-1. In vitro cytokine assays show that LBP reduces levels of proinflammatory cytokines by inhibiting LPS. PEI-DA is synthesized as the gene carrier by conjugation of deoxycholic acid to low-molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Recombinant gp12 (the T4 phage tail adhesin) retains the ability to bind LPS, and gp12 was successfully used in an in vivo experiment to counteract LPS-induced inflammation in rice ( Miernikiewicz et al, 2016 ). Kim et al (2017) demonstrated that a non-toxic LPS binding peptide was an effective anti-inflammatory peptide for the treatment of acute lung injury. Brackett et al (1997) demonstrated that a synthetic peptide corresponding to amino acid residues 20 through 44 of the neutrophil-derived 37-kDa cationic antimicrobial protein (CAP37 P20–44) can bind lipid A of LPS, which could be useful in attenuating in vivo responses induced during endotoxemia, including sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant gp12 (the T4 phage tail adhesin) retains the ability to bind LPS, and gp12 was successfully used in an in vivo experiment to counteract LPS-induced inflammation in rice ( Miernikiewicz et al, 2016 ). Kim et al (2017) demonstrated that a non-toxic LPS binding peptide was an effective anti-inflammatory peptide for the treatment of acute lung injury. Brackett et al (1997) demonstrated that a synthetic peptide corresponding to amino acid residues 20 through 44 of the neutrophil-derived 37-kDa cationic antimicrobial protein (CAP37 P20–44) can bind lipid A of LPS, which could be useful in attenuating in vivo responses induced during endotoxemia, including sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…claimed that increased bacteria-derived 5-hydroxytryptophan (5-HT) in the peripheral circulation activates the formation of pulmonary NETs as well ( 129 ). While, several metabolites from intestinal bacteria, such as bile acids (ocaliva and ursodeoxycholic acid), butyric acid, etc., are proven to have protective effects on PALI ( 130 – 132 ).…”
Section: Mechanisms Of Ali Caused By Intestinal Bacterial Dysbiosismentioning
confidence: 99%
“…Kim et al reported the synthesis of DCA conjugated polyethyleneimine (PEI) through post-polymerization modulation on PEI. [78] Dicyclohexylcarbodiimide (DCC) and NHS were employed during the coupling process. The resultant PEI-DCA material leads to the formation of a ternary complex along with lipopolysaccharide-binding peptide (LBP) and plasmid DNA, for synergistic action in combinatorial therapy.…”
Section: Design Trends Of Deoxycholic Acid-based Polymersmentioning
confidence: 99%